1975
DOI: 10.1111/j.1432-1033.1975.tb04001.x
|View full text |Cite
|
Sign up to set email alerts
|

Studies of Lipopolysaccharides from Pseudomonas aeruginosa

Abstract: Lipopolysaccharides from 13 strains of Pseudomonas aeruginosa representing seven serotypes of the Habs scheme have been analysed. The lipid A fractions, obtained by mild acid hydrolysis of the lipopolysaccharides, contained phosphorylated glucosamine residues substituted with dodecanoic, hexadecanoic, 2-hydroxydodecanoic, 3-hydroxydecanoic, and 3-hydroxydodecanoic acids (hexadecanoic acid and 2-hydroxydodecanoic acid were absent from one lipid A). Low-molecular-weight solutes released during the mild hydrolyse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
70
1

Year Published

1978
1978
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 89 publications
(75 citation statements)
references
References 43 publications
4
70
1
Order By: Relevance
“…It has been shown that S. paratyphi B and S. typhimurium can synthesize a Ti polysaccharide and an 0 polysaccharide attached to the same core (37,41) and that the synthesis of the two molecules is independent (37). Other P. aeruginosa strains may also be able to synthesize more than one type of LPS with different 0-antigenic side chains (8,30,57,58). The highmolecular-weight polysaccharide released from LPS of these strains has been resolved into amino sugar-rich and neutral sugar-rich fractions when separated by gel permeation chromatography (30, 57, 58).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…It has been shown that S. paratyphi B and S. typhimurium can synthesize a Ti polysaccharide and an 0 polysaccharide attached to the same core (37,41) and that the synthesis of the two molecules is independent (37). Other P. aeruginosa strains may also be able to synthesize more than one type of LPS with different 0-antigenic side chains (8,30,57,58). The highmolecular-weight polysaccharide released from LPS of these strains has been resolved into amino sugar-rich and neutral sugar-rich fractions when separated by gel permeation chromatography (30, 57, 58).…”
Section: Discussionmentioning
confidence: 99%
“…charides has been complicated in some cases by chemical heterogeneity of the polysaccharide chains (8,9,30,58). In some instances, the polymeric material has been resolved into amino sugar-rich and neutral sugar-rich fractions (30,58). The biological significance of such fractions is unclear, but a possible explanation is that P. aeruginosa strains produce multiple types of molecules with chemically distinct polysaccharide chains.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Acid-hydrolysed samples of the cleaved polysaccharide (1 M-HCl at 100 "C for 30 min) were chromatographed on plates of silica gel GF (Analtech) in methanol/pyridine/lO M-HCI/ water (32:4: 1 :7, by vol.) (Wilkinson & Galbraith, 1975). Standards of 2,6-diaminopimelic acid and ethanolamine were run with the samples.…”
Section: Bacteriamentioning
confidence: 99%